Determination of Momelotinib in Rat Plasma by LC-MS/MS: Application to Pharmacokinetics Study - Babu, Bysani Suresh; Baby, Nalanda Revu; Mondal, Sumanta (International Journal of Pharmaceutical Investigation, 2025)
Objectives This study describes developing and validating a novel method using LC-MS/ MS to measure the concentration of Momelotinib in rat plasma. Materials and Methods The pharmacokinetic applicability of the process was assessed in rats using a Symmetry C18 column (250 mmx4.6 mm, 5 µm) at room temperature for separation. The mobile phase consisted of a mixture of acetonitrile and 0.1% formic acid (45:55) with a 1.0 mL/min flow rate and an injection volume of 10 µL. The Liquid Chromatography (LC) process was carried out over 5 min, with the mass spectrometer operating in positive ESI mode. The mass-to-charge ratio transitions for Momelotinib and Oclacitinib were determined as m/z 415.4285→160.4698 and 338.2142→266.9137, respectively. Results and Discussion The concentration range for Momelotinib was established at 7.50-60.00 ng/mL, with a correlation coefficient of 0.9999. The precision and accuracy for High-Quality Control (HQC), Medium-Quality Control (MQC), Low-Quality Control (LQC) and Lower Limit of Quantification (LLQC) were 97.52%, 98.97%, 95.46% and 92.55%, respectively. The recovery accuracy for Momelotinib was found to be 97.29%. In pharmacokinetic studies, Momelotinib exhibited an average AUC0-t of 156 ng-hr/mL and a Cmax of 27.2 ng/mL in rats. Conclusion In conclusion, this validated approach effectively demonstrates the determination of pharmacokinetic parameters following the oral administration of Momelotinib in Wistar rats.
Keywords: Momelotinib; Oclacitinib; Bioanalysis rat plasma; Pharmacokinetics.